2022
DOI: 10.1186/s12882-022-02949-7
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of malnutrition risk in elderly patients with acute kidney injury in the intensive care unit

Abstract: Background Malnutrition is common in critically ill patients, but nutrition status in critically ill patients with acute kidney injury (AKI) has been poorly studied. Our study aimed to investigate the relationship between malnutrition risk and the occurrence and prognosis of AKI in elderly patients in the intensive care unit (ICU). Methods Data were extracted from the Beijing Acute Kidney Injury Trial (BAKIT). A total of 1873 elderly patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Our analysis exhibited that decreased GNRI was remarkably associated with elevated mortality risk and prolonged stay length. This was in agreement with the results of the previously published studies: Malnourished AKI patients revealed lower survival rates (21)(22)(23). The BMI and ALB, components of GNRI, demonstrated a strong correlation with the mortality of critically ill AKI patients (24,25).…”
Section: Discussionsupporting
confidence: 92%
“…Our analysis exhibited that decreased GNRI was remarkably associated with elevated mortality risk and prolonged stay length. This was in agreement with the results of the previously published studies: Malnourished AKI patients revealed lower survival rates (21)(22)(23). The BMI and ALB, components of GNRI, demonstrated a strong correlation with the mortality of critically ill AKI patients (24,25).…”
Section: Discussionsupporting
confidence: 92%
“…Based on the available data, it appears that malnutrition status may be a risk factor for AKI in severely ill patients, regardless of their use of CM. Among elderly patients hospitalized in the intensive care unit, the group diagnosed with AKI had a higher risk of malnutrition as assessed by modified Nutrition Risk in Critically Ill (mNUTRIC) compared to the group without AKI [ 57 ]. Further studies may reveal whether the risk of AKI in patients with malnutrition and MVCAD differs depending on the revascularization strategy adopted and the amount of CM used.…”
Section: Risk Factors For Acute Kidney Injury In Patients With Myocar...mentioning
confidence: 99%
“…The population of the original studies was mainly from China [ 10 12 , 17 21 , 23 , 25 , 28 ]; three were from Turkey [ 16 , 22 , 24 , 26 , 27 ], and one was from America [ 15 ]. Among the 17 studies, 11 studies included patients undergoing coronary angiography (CAG) or percutaneous coronary angiography [ 11 , 12 , 16 , 17 , 19 , 21 , 23 – 26 , 28 ], two included patients undergoing coronary artery bypass [ 22 , 27 ], one was related to pediatric severe sepsis [ 15 ], and three included patients with other diseases [ 10 , 18 , 20 ]. Malnutrition was mainly assessed using the CONUT score, geriatric nutritional risk index, Modified Nutrition Risk in Critically Ill Patients score, PNI, and NRS-2002.…”
Section: Resultsmentioning
confidence: 99%